2011
DOI: 10.1111/j.1349-7006.2011.01959.x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variation in APE1 is associated with gastric cancer survival in a Chinese population

Abstract: Altered DNA repair can be associated with aggressive tumor biology and impact on survival of cancer patients. We investigated whether genetic variation of human apurinic/apyrimidinic (AP) endonuclease, a key multifunctional gene involved in the base excision repair pathway, would play a role in gastric cancer survival outcomes. We genotyped APE1 rs1760944 by the TaqMan method in 925 gastric cancer patients. Analyses of association between the polymorphism and survival outcomes were carried out using the Kaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The univariate and multivariate analyses showed that 50 cases with APE1 positive expression correlated with short overall survival in patients during follow-up in 24 months ( P = 0.026 and 0.035) (Tables 1 and 2, Figure 1A and 1C). Additionally, we also found that Her-2 overexpression cases has poor prognosis consistent with results from previous study ( P = 0.041 and 0.048) (Tables 1 and 2, Figure 1B and 1C) [16]. To some extent, APE1 and Her-2 overexpression associated with poor outcome of patients with gastric cancer, indicating potential markers for target therapy in clinical settings.…”
Section: Resultssupporting
confidence: 90%
“…The univariate and multivariate analyses showed that 50 cases with APE1 positive expression correlated with short overall survival in patients during follow-up in 24 months ( P = 0.026 and 0.035) (Tables 1 and 2, Figure 1A and 1C). Additionally, we also found that Her-2 overexpression cases has poor prognosis consistent with results from previous study ( P = 0.041 and 0.048) (Tables 1 and 2, Figure 1B and 1C) [16]. To some extent, APE1 and Her-2 overexpression associated with poor outcome of patients with gastric cancer, indicating potential markers for target therapy in clinical settings.…”
Section: Resultssupporting
confidence: 90%
“…Survival analyses showed a statistically significant (P 0.025, log-rank test) differences in median survival time between gastric cancer patients with APE1 rs1760944 TT (55 months) versus those with GT/GG (78 months). These studies suggest that APE1 polymorphism is a potential biomarker in patients with Gastric cancer [56]. In another study, significant differences in the distribution of APE1 genotype were found between colon cancer patients and healthy individuals.…”
Section: Ape1mentioning
confidence: 90%
“…It has been found genetic variant may be a useful marker for predicting the prognosis of patients with gastric cancer. Previous studies reported PSCA rs2294008 and APE1 rs1760944 are associated with gastric cancer survival [5], [6].…”
Section: Introductionmentioning
confidence: 94%